THE COMBINATION OF SUBTLE EMOTIONS AND DEEP PHILOSOPHICAL VIEWS IN THE POEMS OF ALEXANDER FEINBERG - Ochilova Xurshida Norsaidovna (TADQIQOTLAR, 2026)
Annotation. This article analyzes the unique poems of the poet, writer and translator Alexander Feinberg, who is well known to Uzbek readers. We all know that the poet has the ability to express many meanings in his poems through short lines. That is why these works are still read with love.